MLL1 promotes placental trophoblast ferroptosis and aggravates preeclampsia symptoms through epigenetic regulation of RBM15/TRIM72/ADAM9 axis - Lingling Li; Haining He; Zhenrong Zheng; Xiaolan Zhao (Biology Direct)
Abstract This study explores the epigenetic mechanism of MLL1 regulating trophoblast ferroptosis in preeclampsia (PE). A murine model of PE was established, and HTR-8/SVneo cells were induced by Erastin to establish an in vitro cell model. GSH, MDA, Fe2+, and ROS levels were measured to assess ferroptosis. MLL1, RBM15, TRIM72, ADMAM9, ASCL4, GPX4, and FTH1 expressions were detected by qRT-PCR or Western blot. ChIP analyzed H3K4me3 enrichment and MLL1 enrichment on RBM15 promoter. The binding of YTHDF2 or m6A to TRIM72 mRNA was determined by RIP. TRIM72 mRNA stability was detected after actinomycin D treatment. The binding of TRIM72 to ADAM9 and the ADAM9 ubiquitination level were detected by Co-IP. MLL1 was highly expressed in placental tissues of PE mice. Inhibition of MLL1 improved PE symptoms in mice, repressed ferroptosis in placental tissues, and inhibited Erastin-induced ferroptosis in vitro. MLL1 elevated RBM15 expression by increasing H3K4me3 on RBM15 promoter. RBM15 promoted the binding of TRIM72 to YTHDF2 by enhancing m6A modification on TRIM72 mRNA, thereby repressing TRIM72 expression. TRIM72 bound to ADAM9 and ubiquitinated it for degradation. In conclusion, MLL1 promotes placental trophoblast ferroptosis and aggravates PE symptoms via epigenetic regulation of RBM15/TRIM72/ADAM9 axis.